Customers' managerial expectations and suppliers' asymmetric cost management - LIANG, Peng (Institutional Knowledge at Singapore Management University, 2023)
This paper investigates how managers in the upstream firm (i.e., supplier) adjust their allocations of cost resources in response to managerial expectations of the downstream firms (i.e., customers) on the future demand and prospects. We conduct an empirical analysis to examine the impact of the tone of customers' forward-looking disclosures (FLDs) contained in the Management Discussion and Analysis section of 10-K filings on suppliers' asymmetric cost behaviors, characterizing costs decreasing less for sales fall than increasing for equivalent sales rise (i.e., "cost stickiness"). We show that the degree of suppliers' asymmetric cost management is positively associated with their customers' tone of FLDs. Moreover, such an association is stronger when the suppliers produce more unique products for their major customers. Our inferences remain robust after controlling for the strategic disclosure behavior of the customer firms, ruling out an alternative mechanism of suppliers' own managerial expectations and managerial empire-building incentives. Lastly, using a decision made by the U.S. Supreme Court in 2005 as a quasi-natural experiment setting, we show that the effect of customers' tone of FLDs on suppliers' cost stickiness becomes stronger when FLDs are more informative. To the best of our knowledge, this paper is the first to introduce cost stickiness in the operations management context to capture management's operational decision intervention regarding resource allocation. We also contribute to information sharing literature by highlighting the importance of channels other than the traditional explicit information sharing channel in obtaining demand-relevant information in supply chains.